Bidirectional relationship between anxiety and gastrointestinal symptoms: a case control study - Pokalkar, Ayushi; Geethanjali; Faizan, Mohammad Adil; Jithendra, Govindappagari Venkata; Amit; R., Sateesh Babu; Reddy, Pramod Kumar (International Journal of Research in Medical Sciences, 2025)
Background: Many patients of anxiety manifest lot of gastrointestinal (GI) symptoms in the form of bloating, diarrhoea, heartburn and constipation. Conversely patients suffering from common GI diseases like irritable bowel syndrome have anxiety symptoms. Severity of one can aggravate the other condition. Gut and brain communicate through gut-brain axis. Gut microbiome and hypothalmo-pituitary-adrenal system and a host of metabolic products play an important role in this axis. Methods: Thirty-eight patients with moderate-to-severe GI symptoms and anxiety were evaluated with appropriate scales for diagnosis and severity. The quality of life was also assessed in them. Thirty-eight healthy subjects with no GI symptoms and no/mild anxiety symptoms were similarly evaluated as control group. Results: Key predictors of anxiety severity and GI symptoms severity were statistically analysed. There was a strong link between GI symptoms and anxiety severity and inverse relationship with the quality of life. Conclusions: Evidence suggests a bidirectional relationship between gastrointestinal symptom severity and anxiety, mediated by the gut-brain axis.